KARAKTER PEREMPUAN JAWA DALAM NOVEL INDONESIA BERWARNA LOKAL JAWA: KAJIAN PERSPEKTIF GENDER DAN TRANSFORMASI BUDAYA (The characters of Javanese Women in Indonesian Fictions with Javanese Local Colour: A Gender Perspective and Cultural Transformation Study) - Ismawati, Esti (Balai Bahasa Jawa Barat, 2013)
Penelitian ini bertujuan mendeskripsikan karakter tokoh perempuan Jawa dalam novel Indone- sia berwarna lokal Jawa: kajian perspektif gender dan transformasi budaya. Dua belas novel yang diteliti, yakni Burung-Burung Manyar (BBM) dan Romo Rahadi (RR) karya YB Mangunwijaya, Canting karya Arswendo Atmowiloto, Para Priyayi (PP), Sri Sumarah (SS) dan Bawuk (B) karya Umar Kayam. Ronggeng Dukuh Paruk (RDK), Lintang Kemukus Dini Hari (LKDH), dan Jentera Bianglala (JB) karya Ahmad Tohari, Pada Sebuah Kapal (PSK), Tirai Menurun (TM) karya Nh. Dini, dan Pariyem (P) karya Linus Suryadi AG. Hasil analisis dapat disimpulkan bahwa karakter perempuan Jawa dalam novel yang diteliti mengalami perubahan yang berkaitan dengan transformasi budaya. Mereka bukan konco wingking, melainkan aktif berperan di sektor publik sebagai pencari nafkah keluarga. Mereka juga bukan perempuan biasa yang pasif, melainkan aktif memecahkan masalah kehidupan. Kesetaraan gender dan transformasi budaya terdapat dalam karakter tokoh perempuan Jawa dalam novel Indonesia berwarna lokal Jawa yang diteliti.Abstract:This research is aimed at describing the characters of Javanese women in Indonesian fictions with Javanese local colour related to gender perspective and cultural transformation study. There are twelve novels observed in the research, namely, Burung-Burung Manyar (BBM) and Romo Rahadi (RR) written by YB Mangunwijaya; Canting (C) written by Arswendo Atmowiloto; Priyayi (P), Sri Sumarah (SS), and Bawuk (B) written by Umar Khayam; Ronggeng Dukuh Paruk (RDP), Lintang Kemukus Dini Hari (LKDH); and Jentera Bianglala (JB) written by Ahmad Tohari, Pada Sebuah Kapal (PSK) and Tirai Menurun ( TM ) written by Nh. Dini, and AG Pariyem (P) written by Linus Suryadi. From the analysis, it can be concluded that cultural transformation has occurred in characters of the Javanese women in Indonesian fiction. Female characters in the fiction, which are analyzed above, have played an important role in various aspects of life. They are not only Konco Wingking, but they also take an active role in the public sector as economic actors in a family. They are not the passive women, but women who are creative in solving the problems of life. Gender equality has been obtained by the Javanese female characters in fictions which are analyzed.